Transformational Leadership and Innovative Work Behavior: Testing the Mediating Role of Knowledge Sharing and Work Passion - Udin, Udin; Shaikh, Mohsin (JDM (Jurnal Dinamika Manajemen), 2022)
Organizations face very complex challenges to achieve survival and competitive markets. Therefore, this study mainly aims to examine the impact of transformational leadership on innovative work behavior while considering the mediation role of knowledge sharing as well as work passion in work situations. A total of 201 responses were received from the participants working in stone milling companies in Central Java-Indonesia, and 193 questionnaires were taken into account for the analysis. This study tested the whole model via a path analysis utilizing SmartPLS 3.0. The results indicated that transformational leadership directly did not significantly impact innovative work behavior. However, transformational leadership positively and significantly impacted knowledge sharing and work passion. In addition, knowledge sharing and work passion positively and significantly impacted innovative work behavior. This finding signifies that knowledge sharing and work passion mediated the association between transformational leadership and innovative work behavior.